Birdsong: Is It Music to Their Ears? - Earp, Sarah E.; Maney, Donna L. (Frontiers in Evolutionary Neuroscience, 2012)
Since the time of Darwin, biologists have wondered whether birdsong and music may serve similar purposes or have the same evolutionary precursors. Most attempts to compare song with music have focused on the qualities of the sounds themselves, such as melody and rhythm. Song is a signal, however, and as such its meaning is tied inextricably to the response of the receiver. Imaging studies in humans have revealed that hearing music induces neural responses in the mesolimbic reward pathway. In this study, we tested whether the homologous pathway responds in songbirds exposed to conspecific song. We played male song to laboratory-housed white-throated sparrows, and immunolabeled the immediate early gene product Egr-1 in each region of the reward pathway that has a clear or putative homologue in humans. We found that the responses, and how well they mirrored those of humans listening to music, depended on sex and endocrine state. In females with breeding-typical plasma levels of estradiol, all of the regions of the mesolimbic reward pathway that respond to music in humans responded to song. In males, we saw responses in the amygdala but not the nucleus accumbens – similar to the pattern reported in humans listening to unpleasant music. The shared responses in the evolutionarily ancient mesolimbic reward system suggest that birdsong and music engage the same neuroaffective mechanisms in the intended listeners.